Elevated serum levels of interleukin-10 in adult-onset Still’s disease are associated with disease activity - Sun, Yue; Wang, Zhihong; Chi, Huihui; Hu, Qiongyi; Ye, Junna; Liu, Honglei; Cheng, Xiaobing; Shi, Hui; Zhou, Zhuochao; Teng, Jialin; Yang, Chengde; Su, Yutong (Clinical rheumatology, 2019)
To evaluate the serum levels of the anti-inflammatory cytokine interleukin-10 (IL-10) in patients with adult-onset Still’s disease (AOSD), a rare, systemic, and multigenic inflammatory disease. The serum levels of IL-10, IL-1β, IL-6, IL-18, and TNF-α were examined by electrochemiluminescence assay. The serum levels of IL-10 were higher in AOSD patients than in healthy controls and positively correlated with systemic score, erythrocyte sedimentation rate (ESR), C-reactive protein level (CRP), ferritin, and inflammatory cytokine (IL-1β, IL-6, IL-18, and TNF-α) levels. Moreover, the levels of IL-10 were significantly higher in AOSD patients who had fever, sore throat, rash, lymphadenopathy, splenomegaly, pneumonia, and arthralgia than in patients who did not. IL-10 was increased in AOSD patients and correlated with disease activity. Key Points • In this manuscript, we confirmed the elevated serum levels of the anti-inflammatory cytokine IL-10 in AOSD patients, which was previously poorly defined. • We revealed for the first time that the levels of IL-10 were correlated with disease activity and inflammatory cytokine levels in AOSD.